Population dynamics of bacteria associated with different strains of the pine wood nematode Bursaphelenchus xylophilus after inoculation in maritime pine (Pinus pinaster) - Roriz, Mariana (2012)
For a long time it was thought that Bursaphelenchus xylophilus was the only agent of the pine wilt disease. Recently, it was discovered that there are bacteria associated with the nematodes that contribute to the pathogenesis of this disease, mainly through the release of toxins that promote the death of the pines. Among the species most commonly found, are bacteria belonging to the Bacillus, Pantoea, Pseudomonas and Xanthomonas genera. The main objective of this work was to study the effect of inoculation of maritime pine (Pious pinaster) with four different nematode isolates, in the bacterial population of nematodes and trees, at different stages of disease progression. The monitoring of progression of disease symptoms was also recorded. Also, the identification of bacteria isolated from the xylem of trees and the surface of nematodes was performed by classical identification methods, by the API20E identification system and by sequencing of bacterial DNA. The results showed that for the symptoms progression, the most striking difference was observed for the pines inoculated with the avirulent isolate. C14-5, which led to a slower and less severe aggravation of symptoms than in pines inoculated with the virulent isolates. In general, it was found that bacterial population, inside the tree, increased with disease progression. A superior bacterial quantity was isolated from pines inoculated with the nematode isolates HF and 20, and, comparatively, few bacteria were isolated from pines inoculated with the avirulent isolate. The identification system API20E was insufficient in the identification of bacterial species; Enterobacter cloacae species was identified in 79% of the isolated bacterial colonies and seven of these colonies could not be identified by this method. Molecular identification methods, through bacterial DNA sequencing, allowed a more reliable identification: eleven different bacterial species within the Bacillus, Citrobacter, Enterobacter, Escherichia, Klebsiella, Paenibacillus, Bacillus, Citrobacter, Enterobacter, Escherichia, Klebsiella, Paenibacillus, Pantoea and Terribacillus genera were identified. General bacterial diversity increased with the progression of the disease. Bacillus spp. were predominant at the earlier stage of disease progression and Klebsiella oxytoca at the later stages. Furthermore, bacterial species isolated from the surface of nematodes were similar to those isolated from the Xylem of pines. In the present work new bacterial species were identified which have never been reported before in this type of study and may be associated with their geographical origin (Portugal). P. pinaster, the pine species used in this study, was different from those commonly grown in Japan and China. Furthermore, it was the first time that bacteria were isolated and identified from an avirulent pine wood nematode isolate.